Improving the Teaching Staff Capacity to Integrate EdTech in the Teaching and Learning Processes at Eduardo Mondlane University - Mate, Marisa Jeremias (School of Education, 2023)
Eduardo Mondlane University (UEM) has been implementing training courses in the use of technologies in the teaching and learning process. However, despite the efforts made by the university, the use of these technologies by lecturers at UEM is limited, particularly in faculties outside the main campus. In response to the above-mentioned problem, a new multifaceted, constructivist approach was implemented at UEM, referred to here as the EdTech sub-program. This thesis is the result of the investigation of the effect of the new approach to integrating educational technology at UEM. In 2019, a series of four workshops were piloted through the EdTech sub-program with the purpose of promoting the use of educational technology by lecturers in teaching and learning. This qualitative study was carried out in four faculties. Semi-structured interviews were conducted with 17 participants: 15 lecturers, who took part in the workshops of the EdTech sub-program, distributed across four faculties (Education, Veterinary, Engineering and Sciences) and two members from the EdTech sub-program. Three theories have been explored in this study. The workshops were based on social constructivist learning theory where participants (lecturers) were encouraged to create learning activities in a real-world setting to design learning activities in an authentic context.. Despite this theory-informed workshop design, lecturers did not all change their practice. This can largely be explained by the fact that the participants are adult and had varied skills with educational technology; they felt their courses were too complicated to be delivered only online; assessment structures were not clear; and some lecturers were resistant to change. The second theory is adult learning theory. This theory focuses on the “characteristics” of adult learners and what they bring to the learning process in the form of their experiences, which helps to explain the diverse response to the workshop. Community of practice theory was used as the third theory to explain how some faculties were willing to embrace educational technology and had history with previous projects. In these examples participants shared understandings concerning what educational technology is and how they have motivated other colleagues to use it. Barriers can be overcome through collaboration between the most active users and the most resistant ones to motivate them to use and promote a community of practice of educational technology users. Key findings also indicate that there is a certain resistance among lecturers to the use of educational technologies, justified by the complexity of courses in some disciplines; however, there are also lecturers who rely on technologies in their teaching practices and report that the results are satisfactory and encouraging.